THE IMPORTANCE AND APPLICATION OF FOREIGN EXPERIENCE OF DIGITALIZATION IN THE SECTORAL ECONOMY OF THE REPUBLIC OF UZBEKISTAN - Касымов Саидакмал Саидахролович; Мухитдинов Асрор Акабирович; Карабаев Б. К. (Galaxy International Interdisciplinary Research Journal, 2023)
This article reveals the meaning and essence of the digital economy, examines its impact on the sectoral economy and spheres of society, notes the leading foreign countries and CIS countries in the field of application of digital technologies in the economy, as well as the level of digitalization in Uzbekistan.